Speculative management : stock market power and corporate change - Krier, Dan, 1965- (SUNY series in the sociology of work and organizations., 2005)
"In this work, Dan Krier examines the relationship between two phenomena that dominated the economic scene in the late twentieth century: the rising power of financial markets and the restructuring of American industry. He argues that corporate governance was transformed during this period into speculative teams of stock-optioned executives and activist owners. These teams encouraged a vigorous restructuring of American industry through corporate buyouts, takeovers, reengineering, and downsizing."--Jacket